2019
DOI: 10.3390/molecules24112084
|View full text |Cite
|
Sign up to set email alerts
|

The Role Ionic Liquid [BMIM][PF6] in One-Pot Synthesis of Tetrahydropyran Rings through Tandem Barbier–Prins Reaction

Abstract: Tetrahydropyran (THP) rings are common in several natural products, therefore, various strategies are being developed to synthesize these rings. The present work described the study of a one-pot synthesis of 2,4,6-trisubstituted tetrahydropyran compounds promoted by the ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate [BMIM][PF6] through a Barbier–Prins reaction between allyl bromide and aldehydes. The use of [BMIM][PF6] gave Prins products from several aldehydes in good yields and reaction times. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Batista et al [ 60 ] synthesized an ionic liquid [BMIM][PF 6 ] and examined their catalytic efficiency for the synthesis of pyran analogs using SnCl 2 .2H 2 O by Barbier–Prins reaction between allyl bromide and aldehydes. Prolonged reaction time (8 h) and moderate yields are the drawbacks of the designed pathway (Scheme 16).…”
Section: Different Synthetic Methodologies For Substituted Pyran Deri...mentioning
confidence: 99%
See 1 more Smart Citation
“…Batista et al [ 60 ] synthesized an ionic liquid [BMIM][PF 6 ] and examined their catalytic efficiency for the synthesis of pyran analogs using SnCl 2 .2H 2 O by Barbier–Prins reaction between allyl bromide and aldehydes. Prolonged reaction time (8 h) and moderate yields are the drawbacks of the designed pathway (Scheme 16).…”
Section: Different Synthetic Methodologies For Substituted Pyran Deri...mentioning
confidence: 99%
“…Among the synthesized compounds, compounds bearing 2-furyl, 3-thiophenyl, 4-NO 2 , 4-hydroxy-3-methoxy groups were found to have remarkable IC 50 values. The aldehydes having electron withdrawing groups (EWG) gave high yields in less reaction time in comparison with aldehydes having electron donating substituents (EDG) (Scheme 15) Batista et al [60] synthesized an ionic liquid [BMIM] [PF 6 ] and examined their catalytic efficiency for the synthesis of pyran analogs using SnCl 2 .2H 2 O by Barbier-Prins reaction between allyl bromide and aldehydes. Prolonged reaction time (8 h) and moderate yields are the drawbacks of the designed pathway (Scheme 16).…”
Section: Ionic Liquids Catalyzed Synthesismentioning
confidence: 99%
“…On the other hand, assisted by microwave radiation, the rate of organic reaction is also greatly improved, and simple operation, high yield, simple post-treatment characteristics (Santagada et al, 2009;Sharma et al, 2012). Meanwhile, study has shown that ionic liquid [BMIM][PF 6 ] has a good role in the one-pot synthesis of tetrahydropyran ring in series Barbier-Prins reaction (Batista et al, 2019). Therefore, we tried to synthesize RPDFB RPDFC, RPDFI, RPDFJ in ionic liquid [BMIM][PF 6 ] and microwave-assisted as the continuation of previous research.…”
Section: Chemistrymentioning
confidence: 99%